Funding Liquidity Risk-Profitability Nexus: Evidence from Islamic Rural Banks - Widarjono, Agus (Department of Islamic Banking, 2025)
Purpose– This study examines the effect of funding liquidity risk and several control variables on the profitability of Shariah rural banks (SRBs), with a specific focus on SRBs located on Java Island, Indonesia. Methodology— A panel regression approach is employed to estimate the relationships between funding liquidity risk and profitability. The analysis covers a panel of 98 SRBs from 2019 to 2023 using quarterly data. For further study, SRBs are categorized by their total assets as a proxy of bank size. Findings – The findings document that funding liquidity risk hurts profitability. Smaller SRBs are more vulnerable to funding liquidity risk than larger SRBs. Furthermore, the results highlight the significant roles of financing and operational efficiency in encouraging bank profitability. Implications – The implications of this study recommend that Shariah rural banks must strengthen their management of funding liquidity risk to maintain profitability. Moreover, enhancing fundamental aspects, particularly efficiency, is essential for improving profitability. Originality— This study contributes to Islamic bank empirical studies by including funding liquidity risk variables, in addition to internal bank variables, in its analysis of profitability.